European banking nationalism : state power and troubled banks - Donnelly, Shawn; Pometto, Gaia (New York, NY : Routledge, 2023)
"This book compares the different expression of, and outcomes from, banking nationalism in two European countries to draw wider conclusions about the consequences for Banking Union in Europe and to show how national governments deal (or fail to deal) with international commitments. It reveals how and why one case - Spain - managed to tackle failing banks within EU Banking Union regulations even before they became written in EU law, while the other - Italy - had more persistent problems. The book argues that Spain demonstrates a successful case of liberal economic nationalism, typified by aggressive, early state intervention to restructure Spanish banks, and help from the European Stability Mechanism even in the face of local political opposition. Italy, meanwhile, suffered from weaker, delayed intervention which forced it to confront European institutions with demands for special treatment as a means of externalizing its own internal weakness. This book will be of key interest to scholars, students and professionals in economic policy, Economic and Monetary Union (EMU) and Banking Union in Europe, European and global governance, European/EU studies, European public policy, European public administration, EU law, as well as professionals working in the banking sector"--
Keywords: Economic and Monetary Union; Banks and banking -- Spain; Banks and banking -- Italy; POLITICAL SCIENCE / Public Policy / Economic Policy; POLITICAL SCIENCE / Economic Conditions